2018
DOI: 10.1371/journal.pgen.1007254
|View full text |Cite
|
Sign up to set email alerts
|

Large scale variation in the rate of germ-line de novo mutation, base composition, divergence and diversity in humans

Abstract: It has long been suspected that the rate of mutation varies across the human genome at a large scale based on the divergence between humans and other species. However, it is now possible to directly investigate this question using the large number of de novo mutations (DNMs) that have been discovered in humans through the sequencing of trios. We investigate a number of questions pertaining to the distribution of mutations using more than 130,000 DNMs from three large datasets. We demonstrate that the amount an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 63 publications
4
97
1
Order By: Relevance
“…We find a significantly negative correlation between putatively selected DNMs and the density of conserved sites in one DNM dataset (Jónsson et al 2017), a significantly positive correlation in another dataset (Wong et al 2016), and no correlation in the third dataset (Francioli et al 2015). Such contradictory patterns have been observed before for other genomic variables and likely arise as a consequence of biases in the ascertainment of DNMs (Smith et al 2018). Thus, it is not possible to conclude that the lower coding mutation rate in functionally rich regions is driving our strong negative correlation between θ N and the density of conserved sites.…”
Section: Discussioncontrasting
confidence: 41%
See 4 more Smart Citations
“…We find a significantly negative correlation between putatively selected DNMs and the density of conserved sites in one DNM dataset (Jónsson et al 2017), a significantly positive correlation in another dataset (Wong et al 2016), and no correlation in the third dataset (Francioli et al 2015). Such contradictory patterns have been observed before for other genomic variables and likely arise as a consequence of biases in the ascertainment of DNMs (Smith et al 2018). Thus, it is not possible to conclude that the lower coding mutation rate in functionally rich regions is driving our strong negative correlation between θ N and the density of conserved sites.…”
Section: Discussioncontrasting
confidence: 41%
“…The positive correlation between diversity and our measure of the mutation rate is not surprising given that we expect regions of the genome with high rates of mutation to have high levels of diversity. Previous analyses have suggested that much of the variation in diversity at the 100KB level can be explained in terms of variation in the mutation rate (Smith et al 2018). Non-coding diversity is also positively correlated to the rate of recombination and negatively correlated to the density of conserved sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations